2014
DOI: 10.1007/s11357-014-9677-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of exceptional parental longevity and physical function in aging

Abstract: Offspring of parents with exceptional longevity (OPEL), who are more likely to carry longevityassociated genotypes, may age more successfully than offspring of parents with usual survival (OPUS). Maintenance of physical function is a key attribute of successful aging. While many genetic and non-genetic factors interact to determine physical phenotype in aging, examination of the contribution of exceptional parental longevity to physical function in aging is limited. The LonGenity study recruited a relatively g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 37 publications
3
31
1
Order By: Relevance
“…We have previously reported that OPEL have a healthier phenotype than OPUS, with lower prevalence of chronic illnesses such as hypertension, diabetes mellitus, heart attacks, and strokes (8). Recently, we also showed that OPEL performed better than OPUS on objective and subjective measures of physical function in a cross-sectional analysis in the same cohort (12). Based on these findings, we hypothesized that OPEL may possess genetic "protection" that allows them to have a slower rate of decline in physical function compared to OPUS.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We have previously reported that OPEL have a healthier phenotype than OPUS, with lower prevalence of chronic illnesses such as hypertension, diabetes mellitus, heart attacks, and strokes (8). Recently, we also showed that OPEL performed better than OPUS on objective and subjective measures of physical function in a cross-sectional analysis in the same cohort (12). Based on these findings, we hypothesized that OPEL may possess genetic "protection" that allows them to have a slower rate of decline in physical function compared to OPUS.…”
mentioning
confidence: 67%
“…Covariates were selected based on results from our cross-sectional analysis (12). Presence of depression, diabetes, heart failure, hypertension, myocardial infarction, angina, strokes, Parkinson's disease, chronic obstructive lung disease, and arthritis was used to calculate a global health summary (GHS) as previously described (15).…”
Section: Covariatesmentioning
confidence: 99%
“…Individual study details have been published previously [1418], and are briefly summarized here. LonGenity recruited an Ashkenazi Jewish cohort from New York City (USA) and surrounding counties with the aim of identifying longevity associated genotypes [14].…”
Section: Methodsmentioning
confidence: 99%
“…Both OPEL and OPUS were recruited through systematic searches of publicly available voter registration lists, contacts at synagogues and community organizations, and advertisements in Jewish newspapers. 16 A subset of eligible subjects (n=85) were recruited from the Einstein Aging Study and were cross-enrolled. Potential participants were contacted by mail and then by telephone to assess interest and eligibility.…”
Section: Methodsmentioning
confidence: 99%